Floating crystalline taste particles

By partially or completely coating the crystalline sulfur particles with solid fat, a concentration gradient is created, which solves the problem of taste substances settled in the beverage, and achieves the effect of reducing taste substance content and improving the multi-layer structure and taste of the beverage.

JP7658920B2Active Publication Date: 2025-04-08SOCIETE DES PRODUITS NESTLE SA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021573918
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-26
Filing Date
2020-06-25
Publication Date
2025-04-08
Estimated Expiration
2040-06-25

AI Technical Summary

Technical Problem

The prior art is difficult to reduce the content of certain taste substances, such as sulfur sugars in foods and beverages without reducing the intensity of taste cognition. Especially when preparing multilayer beverages, certain taste substances, such as crystalline sulfur sugars, will settle immediately.

Method used

By partially or completely coating the crystalline sulfur particles with a small amount of solid fat, a concentration gradient is created that makes the taste substance unevenly distributed in the beverage, increasing the sweetness perception at the top while maintaining a low total sulfur concentration.

Benefits of technology

It achieves the reduction of certain taste substances in food and beverages without reducing the intensity of taste cognition, while avoiding the immediate settlement of taste substances, and improving the multi-layer structure and taste of the beverage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658920000007
    Figure 0007658920000007
  • Figure 0007658920000008
    Figure 0007658920000008
  • Figure 0007658920000009
    Figure 0007658920000009
Patent Text Reader

Abstract

A beverage powder comprising crystalline taste particles, characterized in that the crystalline taste particles are at least partially coated with a hydrophobic coating, and the at least partially coated crystalline taste particles have a density of 1 g / cm 3 More than 1.5 g / cm 3 A beverage powder having an average density of less than 10 ...
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [Background technology] Reconstituted powders offer a convenient solution for preparing beverages such as coffee mixes. However, these products often contain high amounts of tastants such as sugar. The increasing consumer demand for healthier food products requires a reduction in the amount of certain tastants. However, a reduction in tastant concentration also leads to undesirable changes in the sensory properties. Previous studies have shown that it is possible to reduce the total amount of tastants (such as sugars, sweeteners, salt, and fats) without reducing taste perception / intensity, provided that a certain stimulation distribution is ensured.

[0002] To apply this concept to powdered beverages, upon reconstitution, a tastant concentration gradient must be achieved with a higher tastant concentration (e.g., sugar) at the top of the cup, which increases the perception of sweetness compared to homogeneously distributed sucrose.

[0003] Amorphous porous particles have been used to deliver tastants to the top of beverages (WO 2018 / 224542 A1). A high closed porosity (10-80%) allows the particles to float on the water surface. They dissolve in the top region, creating a concentration gradient in the beverage. This solution requires special processing to produce sugar in an amorphous state. This amorphous material has a high sensitivity to moisture and temperature compared to its crystalline counterpart; this property does not apply to crystalline materials.

[0004] Multi-layered beverages can be produced by layering liquids of different densities (US Pat. No. 7,013,933 B2). The density of the liquid layers decreases from the bottom to the top of the cup. This principle applies, for example, to cappuccino-type beverages.

[0005] WO 2016 / 071744 A1 describes a tablet (containing a creamer / whitening ingredient, a flavour ingredient and a biscuit ingredient) that is used to form a layered beverage. The effervescent ingredients form a foam on the surface of the beverage, while the dense biscuit ingredient forms the bottom layer. Thus, a layer is formed as a result of the relative densities of the layers.

[0006] WO 2016 / 020367 A1 describes a multi-layer tablet for the formation of a multi-layer beverage. The tablet contains dark ingredients (sugar, coffee and / or cocoa particles, density range: 0.5-0.7 g / cm 3 ) and white component (containing creamer and sugar, density range: 0.74-0.9g / cm 3 ) and

[0007] None of these approaches address the problem that certain tastants, such as crystalline forms of sucrose, immediately sink upon contact with water.

[0008] [Summary of the Invention] Surprisingly, it has been found that by partially or completely coating crystalline sucrose particles with a small amount of solid fat, a concentration gradient is created that can ultimately be used to improve taste perception and reduce the overall sucrose concentration in, for example, powdered food products that are reconstituted by the consumer.

[0009] Suitable hydrophobic coating materials include, for example, cocoa butter, palm fat, butterfat, and coconut fat. The applied coating is such that the overall density of the coated particles is less than 1 g / cm of the density of water. 3 (e.g. 1.59 g / cm for sucrose coated with 0.1% cocoa butter) 3 ) also results in particle levitation.

[0010] The coated sucrose particles can be used as an ingredient in a variety of powdered food products.

[0011] Surprisingly, it has been found that even small amounts of solid fat (e.g. 0.1-0.6% cocoa butter) are sufficient to achieve flotation of the particles. Moreover, the particles do not need to be covered with a complete coating. A partial coating, i.e. a non-homogeneous distribution of the solid fat (fat spots or small areas) is sufficient to achieve flotation behavior. Thus, the particle surface only needs to be partially hydrophobic.

[0012] The reduction in wettability and the corresponding increase in the action of capillary forces were identified as the main contributing factors. The immediate sinking due to high solid density is avoided by the reduction in wettability. Small amounts of solid fat had a large and significant effect on wettability as shown by contact angle measurements. The effect of changes in solid density can be excluded since the amount of lipid applied is not so large as to reduce the particle density below the density of water.

[0013] The described solution can be applied to standard sugar or salt crystals and only requires a (heterogeneous or homogeneous) distribution of hydrophobic material (e.g. solid fat) on the particle surface. The use of crystalline tastants (e.g. crystalline sucrose) is generally associated with high shelf-life and reduced sensitivity to moisture and temperature. Thus, product stability and handling are improved compared to amorphous materials. [Brief description of the drawings]

[0014] [Figure 1] Microscopic images (magnification 50x) of pure spherical sucrose particles (SpR) and coated spherical sucrose particles (SpC1-SpC3). A scale bar of 100 μm is indicated in the lower right corner of each image. [Diagram 2] Scanning electron micrographs of SpR particles recorded at 10 kV. a) 40x magnification, b) 100x magnification. [Diagram 3]Scanning electron micrographs of SpC1 (0.1% cocoa butter) recorded at 10 kV. a) 40x magnification; b) 100x magnification; c) 100x magnification, showing cocoa butter; d) Enlarged image of c, showing cocoa butter. [Figure 4] Scanning electron micrographs of SpC2 recorded at 10 kV. a) 40x magnification; b) 100x magnification; c) 100x magnification, showing cocoa butter; d) Enlarged image of c, showing cocoa butter. [Diagram 5] Scanning electron micrographs of SpC3 recorded at 10 kV. a) 40x magnification; b) 100x magnification, Example 1; c) 100x magnification, Example 2; d) Enlarged image of c; e) 100x magnification, Example 3; f) Enlarged image of e. [Figure 6] Pure sucrose particles falling onto the water surface (left), and a sucrose layer forming at the bottom of the container (right). [Figure 7] Small-scale wetting tests of coated sucrose samples S1–S3. [Figure 8] Images of a single coated particle taken during levitation 1 s after the drop, and the corresponding percentage of particle immersion (average of 10 replicates). [Figure 9] Microscope images of pure sucrose (left) and sucrose coated with 1.2% cocoa butter (right). Scale bars of 1000 μm are indicated in the bottom right corner of each image. [Figure 10] Standard wetting test of pure sucrose (right) and sucrose coated with 1.2% cocoa butter (centre) and "inverse" wetting test of sucrose coated with 1.2% cocoa butter, performed at room temperature. [Figure 11] Standard wetting test of sucrose coated with 1.2% cocoa butter in water at 40°C (left) and 65°C (right) [Figure 12] Microscopic images of samples SP1-SP4 coated with palm fat using high shear mixing. A scale bar of 1000 μm is indicated in the bottom right corner of each image. [Figure 13] Standard wetting test of sucrose coated with different amounts of palm fat using high shear mixing. [Figure 14] Standard wetting test of sucrose coated with different amounts of palm fat using high shear mixing. Carried out at 40°C and 65°C. [Figure 15] Standard wetting test of sucrose coated with 0.8% and 1.3% palm fat using high shear mixing. Conducted at 40°C. [Figure 16] Microscope images of samples SSo1–SSo3 coated with sunflower oil using high shear mixing. A scale bar of 1000 μm is indicated in the bottom right corner of each image. [Figure 17] Standard wetting test of sucrose coated with different amounts of sunflower oil using high shear mixing. [Figure 18] Standard wetting test of sucrose coated with palm fat or cocoa butter.

[0015] [Problem to be solved by the invention] The present invention relates generally to a powdered food product comprising crystalline taste particles, characterized in that the taste particles are at least partially coated with a hydrophobic coating.

[0016] In particular, the present invention relates to a beverage powder comprising crystalline taste particles, the crystalline taste particles being at least partially coated with a hydrophobic coating, and the at least partially coated crystalline taste particles have a hydrophobicity of less than 1 g / cm 3 More than or equal to 1.25 g / cm 3 More than or equal to 1.5 g / cm 3 The present invention relates to a beverage powder having an average density of greater than 1000 g / g.

[0017] In some embodiments, the coated taste particles have a density of 1.2 g / cm 3 ~2g / cm 3 , or 1.3 g / cm 3 ~1.9g / cm 3 , or 1.4 g / cm 3 ~1.8g / cm 3 , or 1.5 g / cm 3~1.7g / cm 3 , or 1.55 g / cm 3 ~1.6g / cm 3 has an average density of

[0018] In some embodiments, the taste-providing particles are sucrose particles.

[0019] In some embodiments, the taste particles have an average size of 200 to 1000 μm, or 300 to 900 μm, or 400 to 800 μm, or 500 to 710 μm.

[0020] In some embodiments, the taste particles are sucrose particles having an average size of 500 to 710 μm.

[0021] In some embodiments, the surface area of ​​the taste particles is, on average, at least 1% coated with the hydrophobic coating, or at least 5%, or at least 10%, or at least 15%, or at least 20%, or at least 40%, or at least 50%, or at least 60%, or at least 70%, or at least 80%, or at least 90% coated with the hydrophobic coating.

[0022] In some embodiments, on average 1% to 50%, or 1% to 20%, or 10% to 20% of the surface area of ​​the taste particles is coated with the hydrophobic coating.

[0023] In some embodiments, the taste particles have a heterogeneous surface chemistry.

[0024] In some embodiments, the surface region of the taste particles comprises at least 5, or 10, or 20, or 30, or 40, or 50 distinct regions of hydrophobic coating.

[0025] In some embodiments, the surface area of ​​the taste particles is on average 1% to 50% coated with the hydrophobic coating and includes on average at least 5 areas of hydrophobic coating.

[0026] In some embodiments, the surface region of the taste particles is completely coated with the hydrophobic coating.

[0027] In some embodiments, the coated taste particles comprise on average at least 98.6% sucrose by weight, or at least 98.8% sucrose by weight, or at least 99% sucrose by weight, or at least 99.2% sucrose by weight, or at least 99.4% sucrose by weight, or at least 99.6% sucrose by weight, or at least 99.8% sucrose by weight.

[0028] In some embodiments, the hydrophobic coating is a solid fat or wax.

[0029] In some embodiments, the coated taste particles comprise on average at least 0.025% by weight of solid fat or wax, or at least 0.05% by weight of solid fat or wax, or at least 0.075% by weight of solid fat or wax, or at least 0.1% by weight of solid fat or wax, or at least 0.3% by weight of solid fat or wax, or at least 0.6% by weight of solid fat or wax, or at least 0.8% by weight of solid fat or wax, or at least 1% by weight of solid fat or wax, or at least 1.2% by weight of solid fat or wax.

[0030] In some embodiments, the hydrophobic coating is a solid fat and has a melting point above about 35°C, about 35-60°C, or about 35-37°C, or about 44-46°C, or about 58-60°C.

[0031] In some embodiments, the hydrophobic coating is a wax and has a melting point of about 62-88°C, or about 62-65°C, or about 82-88°C.

[0032] In some embodiments, the solid fat is selected from cocoa butter, palm fat, butterfat, or coconut fat. In some embodiments, the solid fat is cocoa butter. In some embodiments, the solid fat is palm fat.

[0033] In some embodiments, the coated taste particles contain an average of about 0.1-1.8% cocoa butter, or about 0.1% cocoa butter, or about 0.3% cocoa butter, or about 0.6% cocoa butter, or about 0.9% cocoa butter, or about 1.2% cocoa butter, or about 1.5% cocoa butter, or about 1.8% cocoa butter.

[0034] In some embodiments, the coated taste particles contain, on average, about 0.05-0.6% palm fat, or about 0.1-0.5% palm fat, or about 0.2-0.4% palm fat, or about 0.3% palm fat.

[0035] In some embodiments, the wax is selected from carnauba wax or beeswax.

[0036] In some embodiments, the coated taste particles have an average contact angle with water of greater than 70°, or greater than 80°, or greater than 90°.

[0037] In some embodiments, the coated taste particles have an average contact angle with water of about 100°.

[0038] In some embodiments, the coated taste particles have an average contact angle with water of less than 150°, or less than 140°, or less than 130°, or less than 120°, or less than 110°.

[0039] In some embodiments, the coated taste particles have an average contact angle with water of from 70° to 150°, or from 80° to 140°, or from 90° to 130°.

[0040] In some embodiments, the beverage powder is suitable for reconstitution with a liquid at a temperature below about 82°C, or below about 62°C, or below about 58°C, or below about 44°C, or below about 35°C, or below about 30°C, or below about 23°C.

[0041] In some embodiments, the beverage powder is suitable for reconstitution with water, milk, coffee, or chocolate milk.

[0042] The present invention also relates to a method for coating crystalline taste particles with a hydrophobic coating, preferably a solid fat or wax.

[0043] In some embodiments, the method comprises: a. fluidizing the crystalline taste particle group; b. applying a hydrophobic coating, preferably melted or tempered cocoa butter, to the taste particles, preferably by spraying; c. fluidizing and solidifying the hydrophobic coating, preferably at 20-25°C; Includes.

[0044] In some embodiments, the nebulization time is at least 4 minutes, or at least 6 minutes, or at least 9 minutes, or about 10 minutes.

[0045] In some embodiments, the method comprises: a. mixing the crystalline taste particles with oil or melted fat or tempered fat, preferably using a high shear mixer, preferably at about 300 rpm; b. spreading the mixture as a powder layer; c. storing the mixture at about 70° C. for about 20 to 25 minutes; d. mixing, preferably for 5 minutes, preferably at about 300 rpm; e. spreading the mixture as a layer and allowing the mixture to solidify; Includes.

[0046] In some embodiments the fat is cocoa butter, preferably in a final amount of 0.1-1.2% by weight, preferably about 1.2% by weight.

[0047] In some embodiments the fat is palm fat, preferably in a final amount of 0.2-0.3% by weight, preferably about 0.3% by weight.

[0048] The present invention also relates to coated crystalline taste particles obtainable by the method described herein.

[0049] The present invention also relates to the use of coated crystalline taste particles in a powdered food product, preferably a beverage powder.

[0050] [Mode for carrying out the invention] As used herein, the term "about" means approximately, in the region of, roughly, or in the vicinity of. When the term "about" is used in conjunction with a numerical value or range, it modifies that value or range by expanding the boundaries above and below the numerical value(s) set forth. . for The term "about" is used herein to describe a numerical value by 10 or less than the stated value. % repair is used to correct

[0051] As used herein, a powdered food product may be a beverage powder (e.g., coffee, coffee mix, milk powder, chocolate powder, infant formula, malt beverage powder), soup powder, or sauce powder.

[0052] As used herein, "crystalline particles" or "crystalline taste particles" are characterized by the fact that the positions of atoms have a three-dimensional long-range order. The atoms of a crystal are arranged in a translationally periodic sequence. In contrast, amorphous particles have a non-periodic sequence with highly disordered atomic positions.

[0053] Crystalline solids are characterized by having a melting point, where the transition between the solid and liquid states occurs (the T of an amorphous solid). g (compared to 83-85%). Crystalline solids dissolve when a critical relative humidity is reached (e.g. 83-85% for sucrose). Below this value, only small amounts of water can be found in the crystals (stored as water of crystallization in the crystalline matrix).

[0054] As used herein, the term "tastant" refers to a substance that stimulates the sense of taste. Tastants are used in foods and beverages to achieve a desired taste profile. Examples of crystalline taste particles include sugar and salt.

[0055] Taste includes the five established basic tastes: sweet, sour, salty, bitter, and umami. As used herein, the term taste is distinct from aroma (detected by the nose) and flavor, of which taste and aroma are components. Tastant-containing particles may further comprise aroma. Tastants according to the present invention may provide a taste selected from the group consisting of sweet, salty, and umami, for example, the tastant may be sweet or salty.

[0056] The tasty particles of the present invention are preferably sweet, for example sucrose, lactose, maltose, glucose, fructose, isomaltulose, galactose, and allulose. In one embodiment, the tasty particles are sucrose. In one embodiment, the tasty particles are polyols. In one embodiment, the tasty particles are rare sugars. The tastant of the present invention may be salty. In one embodiment, the tasty particles are sodium chloride.

[0057] As used herein, the term "hydrophobic coating" refers to a structure in which a core material (here a tastant) is either completely or partially covered with a hydrophobic coating material (shell / capsule / wall material), resulting in reduced wettability or decreased wetting behavior.

[0058] The term wettability describes the affinity (molecular interaction) between a solid and a liquid, preferably water, and is generally evaluated via the solid-liquid contact angle, which reflects the degree of wetting when a liquid comes into contact with a solid.

[0059] The applied hydrophobic coating material is characterized by a low wettability by water. There is a low affinity between the hydrophobic material and water. Water tends to reduce the contact area with the solid. This corresponds to a high contact angle. Hydrophobic materials are generally characterized by a contact angle with water of greater than 90°.

[0060] A variety of hydrophobic materials can be used as coating agents. In some embodiments, the hydrophobic material includes solid fats such as palm fat, cocoa butter, milk fat, etc. In some embodiments, the hydrophobic material includes waxes such as beeswax, carnauba wax, etc. In some embodiments, the hydrophobic material includes fatty acids. Hydrophobicity is influenced by the structural characteristics of the hydrocarbon chain. The longer and less saturated the hydrocarbon chain, the more hydrophobic and the less water soluble it is.

[0061] Examples of suitable coating materials: [Table 1]

[0062] The coating process can be carried out using a variety of techniques, which in some embodiments include fluidized bed coating, high shear mixing, drum coating, spray chilling / spray cooling.

[0063] As used herein, the term "solid fat" refers to a lipid that is solid at room temperature. Lipids are generally defined as materials that are insoluble in water but soluble in non-polar solvents, and include fats and oils, waxes, and phospholipids, among others.

[0064] Solid fats are characterized by a solid fat content that results in a melting temperature above ambient temperature. In contrast, oils are liquid at room temperature. Solid fats include, for example, palm fat, cocoa butter, milk fat, coconut fat, and shea butter.

[0065] Fats are usually composed of a mixture of lipids, mainly triacylglycerols (generally more than 95%), diacylglycerols and monoacylglycerols, free fatty acids. Further components such as phospholipids, tocopherols and fat-soluble vitamins are typically present. Fats and oils are hydrophobic and therefore essentially insoluble in water. The solid fat content can be measured according to the method ISO 8292-1:2008.

[0066] As used herein, the term "sphericity" is defined as the ratio of the surface of a sphere of equivalent volume to the actual surface of the particle. For ideal spherical particles, the ratio approaches 1.

[0067] [Example] Example 1 Coating Process Methodology Coating of the particles can be carried out in a variety of ways. Two methods suitable for preparing levitating particles are described below.

[0068] Fluid Bed Coating: Using fluidized bed technology, crystalline sucrose particles were coated with various amounts of cocoa butter. The sucrose particles were fluidized in a process chamber and molten cocoa butter (approximately 70°C) was sprayed on top. After spraying, the powder was continuously fluidized for 10 minutes (fluidization air temperature of 20-25°C) to allow the cocoa butter to solidify. Using this method, precise amounts of coating can be prepared.

[0069] High shear mixing: Crystalline sucrose particles were coated with various amounts of fat / oil using a benchtop food processor (Kenwood) equipped with a custom-built high shear mixer impeller (University of Sheffield). The impeller speed was controlled by a 240V, 7Amp regulator (University of Sheffield). The sucrose particles were mixed in a mixing vessel at approximately 300 rpm and oil (RT) or molten fat (70°C) was slowly poured on top. After the liquid oil / fat was added, the powder was mixed continuously at approximately 300 rpm for 5 minutes. The samples were then removed from the mixing vessel, spread as a powder layer, and stored at 70°C for 20-25 minutes. This procedure was chosen to melt the solid fat and reduce the amount of lumps in the mixture. A second mixing step was then performed at 300 rpm for 5 minutes. The samples were then spread as a thin layer and allowed to solidify overnight at ambient temperature.

[0070] Example 2 Fluid bed coating of cocoa butter onto sucrose spheres Spherical sucrose particles (Nonpareil 103) were coated with a small amount of cocoa butter using the fluidized bed technique. The composition and density of the samples (SpC1-SpC3) are shown in Table 1. The fat content was determined by fat extraction. Pure crystalline sucrose spheres (SpR) were used as a reference material. Due to the small amount of cocoa butter applied, the particle density does not vary significantly.

[0071] [Table 2]

[0072] As shown in the microscopic images, there are no visible differences in the appearance of the reference and coated samples (Figure 1). SEM images of the pure and coated particles are shown in Figures 2-5. Surface coverage by cocoa butter is not clearly visible for samples SpC1 and SpC2. Only specks of cocoa butter can be observed on the surface of some particles. A different observation was made for the particles of sample SpC3. For the majority of the particles, the particle surface appears to be almost completely covered with cocoa butter.

[0073] Example 3 Effect of cocoa butter coating on wettability The apparent contact angle was measured using the sessile drop method. A layer of coated powder was fixed to an adhesive tape and a liquid drop was placed on the powder layer. For pure sucrose, tablets were pressed (pressure: 20 kN, compaction speed: 10 mm / min) and a liquid drop was placed on the tablet. The contact angle was measured using a goniometer.

[0074] The measured apparent contact angles are shown in Table 2. Particle coating significantly increased the apparent contact angle. Increasing the cocoa butter content increased the apparent contact angle.

[0075] [Table 3]

[0076] Example 4 Effect of cocoa butter coating on the flotation of powders and particles. The flotation behavior was investigated using a microscopy technique. A polystyrene cuvette filled with 3.5 mL of distilled water (23 ± 1 °C) was placed in front of a tilted microscope lens and 0.19 g of sample was dropped onto the water surface. Using the same setup, the flotation of each sample was investigated at the single particle level.

[0077] Pure sucrose sank immediately upon dropping onto the water surface (Figure 6). The flotation behavior of samples SpC1-SpC3 at different time points after dropping is shown in Figure 7. All coated samples showed flotation behavior. It was confirmed that the amount of flotation powder and the flotation / dissolution time depended on the amount of coating. Analysis of single particle flotation revealed that the particle immersion depth decreased with increasing amount of coating (Figure 8).

[0078] Example 5 Fluid Bed Coating of Cocoa Butter onto Standard Sucrose Standard crystalline sucrose (Schweizer Zucker AG) was coated with 1.2±0.1% cocoa butter (calculated by fat extraction) using a fluidized bed process. Pure crystalline sucrose was used as a reference material. A microscopic image of the sample is shown in FIG. 9 at 50x magnification. The coating does not cause any obvious change in the appearance of the sucrose.

[0079] Example 6 Effect of cocoa butter coating on powder flotation Powder floatation / sinking was evaluated using a standard wetting test. For the test, 15 g of sample was added to a steel funnel (diameter 3 cm). The funnel was placed on a glass plate on top of a beaker (diameter 7 cm). The glass beaker contained 200 mL of water (RT). The glass plate was manually pulled out to observe the wetting and sinking behavior of the powder. Additionally, the dispersed powder was manually mixed after 10 min to evaluate the floatation behavior after mixing.

[0080] Pure sucrose immediately sinks upon contact with water, forming a layer of sucrose at the bottom of the beaker (Figure 10, left). Coated sucrose behaves quite differently. Most of the powder floats to the liquid surface. It is further observed that the remaining powder subsequently rises to the surface. After 10 minutes, only a small amount of powder remains at the bottom of the beaker. Even after mixing, the rise of powder to the surface of the beaker can be observed (Figure 10, center).

[0081] To further evaluate the flotation behavior of the coated powder, a "reverse wetting test" was performed. First, the powder (15 g) was added to a beaker (diameter: 7 cm). Then, 200 mL of water (RT) was poured on top. The flotation and movement of the powder was observed for 10 minutes.

[0082] As previously observed, pure sucrose forms a layer at the bottom of the beaker. In contrast to this result, some of the coated powder floats to the surface immediately upon addition of water. A continuous rise of the powder from the bottom of the beaker to the surface is observed (Figure 10, right).

[0083] Standard wetting tests were further carried out at water temperatures of 40°C and 65°C (Figure 11). With increasing water temperature, sucrose immediately sank, which can be explained by the melting of cocoa butter (melting point: 35-37°C).

[0084] Example 7 Coating palm fat onto standard sucrose using high shear mixing Standard sucrose (Schweizer Zucker AG, size class 500-710 μm) was coated with a small amount of palm fat (CLSP, 555, fully hydrogenated palm kernel oil, solid fat at 20 °C: 93-97%) using high shear mixing. The composition of the samples produced is shown in Table 3. The fat content was determined by solvent extraction with n-heptane at room temperature. Pure crystalline sucrose was used as a reference material. No differences in the appearance of each sample are observed, as shown in the microscopic images (Figure 12).

[0085] [Table 4]

[0086] Example 8 Effect of palm fat coating on powder flotation. Powder float / sink was evaluated using a standard wetting test. For the test, 15 g of sample was added to a steel funnel (diameter 3 cm). The funnel was placed on a metal plate above a beaker (diameter 7 cm, powder drop height 4.5 cm). The glass beaker contained 200 mL of water (23±1°C). The plate was manually withdrawn and the float / sink behavior of the powder was recorded. Additionally, the dispersed powder was manually mixed after 10 min and the float behavior after mixing was evaluated.

[0087] The floating behavior over time of samples SP1-SP4 is shown in Figures 13-15. Coated sucrose behaved quite differently to pure sucrose (which immediately sinks, Figure 13). With increasing fat content, the amount of floating powder increases. For samples SP1 and SP2, part of the powder sinks on contact with water. Over time, the rise of the powder to the water surface can be observed. For samples SP3 and SP4, the entire amount of powder floated to the water surface. After manual mixing, the rise of the powder to the water surface could be observed for each sample.

[0088] Example 9 Coating of sunflower oil onto standard sucrose using high shear mixing Standard sucrose (Schweizer Zucker AG, size class 500-710 μm) was coated with a small amount of sunflower oil using high shear mixing. The composition of the samples produced is shown in Table 4. The oil content was determined by solvent extraction with n-heptane at room temperature. Pure crystalline sucrose was used as a reference material. No differences in the appearance of each sample are observed, as shown in the microscopic images (Figure 16).

[0089] [Table 5]

[0090] Example 10 Effect of sunflower oil coating on powder flotation. Powder float / sink was evaluated using a standard wetting test. For the test, 15 g of sample was added to a steel funnel (diameter 3 cm). The funnel was placed on a metal plate above a beaker (diameter 7 cm, powder drop height 4.5 cm). The glass beaker contained 200 mL of water (23±1° C.). The plate was manually pulled out and the float / sink behavior of the powder was recorded.

[0091] All samples sank immediately upon contact with water, as shown in Figure 17. The sunflower oil coating did not result in powder flotation.

[0092] Example 11 Flotation of coated powders in milk, coffee, and chocolate milk Palm fat and cocoa butter coated powders were evaluated for powder floatation / sinking in milk, coffee and chocolate milk. A summary of the solid and liquid combinations is shown in Table 5.

[0093] [Table 6]

[0094] Floating was evaluated using a standard wetting test, as shown in Figure 18. For the test, 15 g of sample was added to a steel funnel (diameter 3 cm). The funnel was placed on a metal plate above a beaker (diameter 7 cm, powder drop height 4.5 cm). The glass beakers contained 200 mL of milk, coffee, or chocolate milk (21 ± 1 °C), respectively. The plate was manually pulled out and the floating / sinking behavior of the powder was recorded. [1] A beverage powder comprising crystalline taste particles, the crystalline taste particles being at least partially coated with a hydrophobic coating, the at least partially coated crystalline taste particles having a hydrophobicity of less than 1 g / cm 3 The beverage powder has an average density of ultra. [2] The at least partially coated crystalline taste particles have a density of 1.5 g / cm 3 The beverage powder according to [1], having an average density of greater than or equal to 1000 g / l. [3] The beverage powder according to [1] or [2], wherein the taste-exhibiting particles are sucrose particles. [4] The beverage powder according to any one of [1] to [3], wherein an average of 1% to 50% of the taste-exhibiting particles are coated with a hydrophobic coating. [5] The beverage powder described in any one of [1] to [4], wherein the hydrophobic coating is a solid fat or a wax. [6] The beverage powder described in [5], wherein the melting point of the solid fat or wax is greater than about 35°C. [7] The beverage powder described in [5] or [6], wherein the solid fat is selected from cocoa butter or palm fat. [8] The beverage powder described in [7], wherein the coated flavor particles contain, on average, about 1.2% cocoa butter. [9] The beverage powder according to [7], wherein the coated taste-providing particles contain, on average, about 0.3% palm fat.

[10] The beverage powder according to any one of [1] to [9], wherein the coated taste particles have an average contact angle with water of more than 70°.

[11] The beverage powder described in any one of [1] to

[10] , wherein the beverage powder is suitable for reconstitution with a liquid at a temperature of about 23°C.

[12] a. Fluidizing the crystalline taste particle group; b. applying a hydrophobic coating, preferably melted or tempered cocoa butter, to said taste particles, preferably by spraying; c. fluidizing, preferably at 20-25° C., to solidify the hydrophobic coating; 20. A method for coating crystalline taste particles with a hydrophobic coating comprising:

[13] a. mixing the crystalline taste particles with oil or melted fat or tempered fat, preferably using a shear mixer, preferably at about 300 rpm; b. spreading the mixture as a powder layer; c. storing the mixture at about 70° C. for about 20 to 25 minutes; d. mixing, preferably for 5 minutes, preferably at about 300 rpm; e. spreading the mixture into a layer and allowing it to solidify; 1. A method for coating crystalline taste particles, comprising:

[14] The method for coating crystalline particles described in

[12] , wherein the solid fat is cocoa butter in a final amount of about 1.2% by weight.

[15] The method for coating crystalline particles according to

[13] , wherein the solid fat is palm fat in a final amount of about 0.2 to 0.3% by weight.

[16] A group of coated crystalline taste particles obtained by the method according to any one of

[12] to

[15] .

[17] Use of the coated crystalline taste particles according to

[16] in a powdered food product, preferably a beverage powder.

[18] A powdered food product comprising the coated crystalline taste particles obtained by the method according to any one of

[12] to

[15] .

Claims

1. A beverage powder comprising crystalline taste particles, the crystalline taste particles being at least partially coated with a hydrophobic coating, the at least partially coated crystalline taste particles having a hydrophobicity of less than 1 g / cm 3 having an average density of 10. A beverage powder, wherein said hydrophobic coating consists solely of cocoa butter, palm fat, butterfat, coconut fat, carnauba wax, or beeswax.

2. The at least partially coated crystalline taste particles have a density of 1.5 g / cm 3 2. The beverage powder of claim 1 having an average density of greater than 1000g / g.

3. The beverage powder according to claim 1 or 2, wherein the taste-providing particles are sucrose particles.

4. 4. The beverage powder according to claim 1, wherein on average 1% to 50% of the surface area of ​​the taste particles is coated with a hydrophobic coating.

5. 10. The beverage powder of claim 1, wherein the cocoa butter, palm fat, butterfat, coconut fat, carnauba wax, or beeswax has a melting point greater than about 35°C.

6. 6. Beverage powder according to claim 1 or 5, wherein the hydrophobic coating consists exclusively of cocoa butter or palm fat.

7. 7. The beverage powder of claim 6, wherein the coated taste particles contain on average about 1.2% cocoa butter.

8. 7. The beverage powder of claim 6, wherein the coated taste particles contain on average about 0.3% palm fat.

9. 9. The beverage powder according to any one of claims 1 to 8, wherein the coated taste particles have an average contact angle with water of more than 70°.

10. a. fluidizing the crystalline taste particles; b. applying a hydrophobic coating to the taste particles; c. fluidizing to solidify the hydrophobic coating; The hydrophobic coating comprises only cocoa butter, palm fat, butterfat, coconut fat, carnauba wax, or beeswax, and the coated crystalline taste particles have a density of 1 g / cm 3 A method for coating crystalline taste particles having an average density of greater than 100% with a hydrophobic coating.

11. a. mixing crystalline taste particles with molten fat or tempered fat; b. spreading the mixture as a powder layer; c. storing; d. mixing; e. spreading the mixture into a layer and allowing it to solidify; A method for coating crystalline taste particles with a hydrophobic coating, comprising: The hydrophobic coating is composed of only cocoa butter, palm fat, butterfat, or coconut fat, and the coated crystalline taste particles have a density of 1 g / cm 3 The method has an average density of greater than or equal to 100 nm.

12. 11. The method of claim 10, wherein the hydrophobic coating is about 1.2% by weight of cocoa butter in a final amount.

13. 12. The method of coating crystalline taste particles with a hydrophobic coating according to claim 11, wherein the hydrophobic coating is palm fat in a final amount of about 0.2-0.3% by weight.

Citation Information

Patent Citations

  • Reverage mixture

    JP1990234640A

  • Drying base and its preparation

    JP1993076287A

  • Improvement of cold water solubility of powders

    JP2010524478A

  • Method for producing granular cocoa

    JP2015202079A